Subject Matter Complexity and Disclosure Channel Richness - Skinner, A. Nicole (The Accounting review, 2024)
Despite the increase in and diversity of disclosure channels available, our understanding of how managers incorporate channel features into their disclosure decisions remains incomplete. I provide evidence that managers choose relatively rich channels that offer multiple cues, opportunities for interaction, and linguistic diversity (i.e., the earnings call, as compared to the press release) to communicate complex information. The positive relation between disclosure channel richness and subject matter complexity persists in both a document-level analysis and a small sample test examining disclosure channel choice from all possible disclosure channels. I provide some evidence that deviating from the complexity/richness matching strategy is associated with a muted market response to firms’ quarterly disclosures. The results are consistent with managers choosing disclosure channels to reduce investors’ information processing costs. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: G14; M41.